2014
DOI: 10.1371/journal.pone.0101894
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Lead Exposure Alters Synaptogenesis through Inhibiting Canonical Wnt Pathway In Vivo and In Vitro

Abstract: Lead (Pb) exposure has been implicated in the impairment of synaptic plasticity in the developing hippocampus, but the mechanism remains unclear. Here, we investigated whether developmental lead exposure affects the dendritic spine formation through Wnt signaling pathway in vivo and in vitro. Sprague–Dawley rats were exposed to lead throughout the lactation period and Golgi-Cox staining method was used to examine the spine density of pyramidal neurons in the hippocampal CA1 area of rats. We found that lead exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 56 publications
3
55
0
Order By: Relevance
“…However, the amount of nano-TiO 2 being released into the ecosystem is increasing (Robichaud et al, 2009), and the bioaccumulation and potential impact of NPs deserve attention. Previous reports revealed that Pb causes changes to N-methyl-d-aspartate receptor (NMDAR) complexes, AChE, ACh and spine density of brain development in rat hippocampus and the significant histopathological changes in fish tissue (Guilarte and McGlothan, 2003;Reddy et al, 2007;Ahmed et al, 2014;Hu et al, 2014). A low dose Pb can similarly decrease the expression of NMDAR to inhibit the synapse development (Nihei et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the amount of nano-TiO 2 being released into the ecosystem is increasing (Robichaud et al, 2009), and the bioaccumulation and potential impact of NPs deserve attention. Previous reports revealed that Pb causes changes to N-methyl-d-aspartate receptor (NMDAR) complexes, AChE, ACh and spine density of brain development in rat hippocampus and the significant histopathological changes in fish tissue (Guilarte and McGlothan, 2003;Reddy et al, 2007;Ahmed et al, 2014;Hu et al, 2014). A low dose Pb can similarly decrease the expression of NMDAR to inhibit the synapse development (Nihei et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the altered TH levels may cause several developmental defects, particularly to the central nervous system (CNS). There were also some results had demonstrated lead could cause an damage to the CNS (Guilarte and McGlothan, 2003;Reddy et al, 2007;Ahmed et al, 2014;Hu et al, 2014). The mechanisms behind the known effects of Pb on the CNS have not been fully explained, but several studies have reported that Pb exposure may alter the hypothalamic-pituitary-thyroid axis and thus, affect the CNS (Meeker et al, 2009;Singh et al, 2000Singh et al, 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Pb-induced decrease in NR2A-containing NMDA receptor expression and phosphorylation of GluR1 could be important for spine formation and morphological change. In a recent study, Pb exposure during lactation period decreased dendritic spine density by inhibiting the Wnt 7a pathway [35]. However, Wnt 5a pathway (but not Wnt 7a pathway) has numerous cross-talks with NMDA receptor signaling [36].…”
Section: Dendritic Spine Density Morphological Change and Glutamatementioning
confidence: 96%
“…In cultured rat hippocampal neurons, low levels of Pb2+ (0.1 and 1 µM) cause reduction of dendritic spine density in a dose-dependent manner (Hu et al, 2014). In a similar in vitro model, exposure to 1 μM Pb2+ for 5 days during the period of synaptogenesis (DIV7-DIV12), significantly reduces proBDNF protein and extracellular levels of mBDNF .…”
Section: Pb2+mentioning
confidence: 89%
“…Exposure of rats to Pb2+ that initiated at embryonic phase and terminated at PND 21 have revealed that at PND 14 (Pb2+ concentration in the hippocampus 0.249±0.06 µg/g) and PND 21 (Pb2+ concentration in the hippocampus 0.471±0.11 µg/g) the number of dendritic spine on hippocampal CA1 area decreases by 32.83% and 24.11%, respectively (Hu et al, 2014). The length-density of the doublecortin-positive apical dendrites in the outer portion of the dentate gyrus molecular layer has been found significantly decreased up to 36% in chronically exposed rats to environmentally relevant levels of Pb2+ (Pb2+ blood levels 25.8 ± 1.28 μg/dL) (Verina et al, 2007).…”
Section: Pb2+mentioning
confidence: 99%